Letter: direct‐acting agent therapy and HCV‐related Child C cirrhosis. Issue 4 (14th July 2017) - Braillon, A.
Abstract : Linked Content This article is linked to Braillon paper. To view this article visithttps://doi.org/10.1111/apt.14184 .